Inorganic Polymeric Nanocomposites and Membranes - Abe, Akihiro.; Abe, Akihiro.; Dusˇek, Karel.; Dusˇek, Karel.; Kobayashi, Shiro.; Kobayashi, Shiro. (Advances in Polymer Science,, 2005)
This series presents critical reviews of the present and future trends in polymer and biopolymer science including chemistry, physical chemistry, physics and materials science. It is addressed to all scientists at universities and in industry who wish to keep abreast of advances in the topics covered. Impact Factor Ranking: Always number one in Polymer Science. More information as well as the electronic version of the whole content available at: springerlink.com.